Determinan Penyebab Kemiskinan Petani dan Kontribusi Usaha Kopra Terhadap Pendapatan Rumahtangga Petani - Marnex Bokaraman; Hendri D Hahury; Rukmin W Payapo; Hermi Oppier (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Abundant availability of natural resources is not a guarantee for the welfare of community who live around them. The natural resources in archipelagic areas have their own diversity, both in terms of their utilization types and patterns. Coconut plants in the copra farming is one of the examples. This study aims to analyze determinants of poverty of copra farmers and contribution of copra farming to farmer household income. The research was conducted in Labuan Village, Nort West Seram District, Central Maluku Regency. There was a total of 35 respondents consisting of copra farmers participating in this study in April – June 2022. Data collection techniques were carried out through interviews, observation and questionnaires with the primary data source coming from copra farmers in Labuan Village. While data analysis is done by first calculating production costs, receipts, income analysis and business contributions. The results show that the copra farming was the income for the farmer households reaching IDR 4,794,304 and the production cost reached IDR 972,273. However, the copra farming contribution to the farmer household income was still relatively low at only 3.49%. Meanwhile, the determinants of poverty of copra farmers included limited access to assets, lack of capital, poor level of skills, and limited markets. As a result of these vulnerabilities, the farmers were required to look for new alternative income sources as a strategy to maintain their household livelihood.